UJI AKTIVITAS ANTIOKSIDAN HASIL FRAKSINASI EKSTRAK METANOL DAUN ILALANG (Imperata cylindrica Linn.) DENGAN METODE DPPH - Munadi, Rachmin; Jasmiadi; Ruslan, Ega Rossalinda (Universitas Cokroaminoto Palopo, 2024)
Research on the antioxidant activity of fractionated illalang (Imperata cylindrica Linn.) leaf extract using the DPPH method has been carried out. This research aims to determine the IC50 value of the n-Hexane fraction and the 70% ethanol fraction from the methanol extract of thatch leaves using the DPPH method. The research method was carried out by maceration extraction using methanol filter fluid. The methanol extract was fractionated using n-Hexane and 70% ethanol to produce n-Hexane and 70% ethanol fractions. The antioxidant activity test of methanol extract, n-Hexane fraction and 70% ethanol was carried out using the DPPH method. The results of the antioxidant activity test of the methanol extract of Illang leaves and the 70% ethanol fraction obtained an IC50 value of 14,786 μg/mL and 11,588 μg/mL respectively, classified as a very strong antioxidant, while the n-Hexane fraction obtained an IC50 value of 100,371 μg/mL and was classified as an antioxidant. strong.